The impact of spoken speech on customer trust: An applied study in the Saudi Arabian Airlines Company during the year 1444 AH - Al-Shahrani, Mohamed Saad Maeed AlZuhair (Journal of Economic, Administrative and Legal Sciences, 2024)
The aim of the research is to detect the level of use of the spoken word (credibility of the spoken word, the content of the spoken word, the source of the spoken word) in the promotion in the Saudi Arabian Airlines Company, and the aim of revealing the level of customer confidence in Saudi Arabian Airlines, and the aim of the research is to identify the impact of the spoken word on customer confidence in Saudi Arabian, To achieve the research objectives, the researcher used the analytical descriptive approach, using the identification as a tool to collect data from a simple random sample of Saudi Arabian Airlines customers consisting of 310 individuals, and the data was unloaded on the SPSS program, The research reached a set of results, the most important of which are: that the level of reliance on the spoken word in Saudi Arabian Airlines was high, and the level of customer confidence in Saudi Arabian Airlines was high, and finally the results showed that there is an impact of the spoken word and its dimensions on customer confidence in Saudi Arabian Airlines, The researcher recommended the need for Saudi Arabian Airlines to form information about its services provided to customers by creating dialogues and conversations between individual customers, as well as it is necessary for Saudi Arabian Airlines to provide quality and distinctive services to customers, and The need for attention to diverse groups of society in service delivery.